1973
DOI: 10.1002/1097-0142(197304)31:4<948::aid-cncr2820310428>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy study of granulocytic sarcoma (chloroma) in patients with myelogenous leukemia, hiroshima-nagasaki 1949-1969

Abstract: Granulocytic sarcoma (chloroma) was present in 23 of 338 myelogenous leukemia patients autopsied in Hiroshima and Nagasaki during 1949‐1969. There was no evidence that granulocytic sarcoma was more frequent among those who received heavy atomic‐bomb irradiation, although the incidence of myelogenous leukemia was greatly increased in the heavily irradiated group compared with controls. Granulocytic sarcoma was found in 19 of 237 persons with acute myelogenous leukemia, in 3 of 77 with chronic myelogenous leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
187
0
8

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(201 citation statements)
references
References 6 publications
6
187
0
8
Order By: Relevance
“…2,3 This review revealed that the other preferential sites were small intestine, mediastinum, epidural site, uterus, and ovary, i.e., sites often difficult for the detection and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 This review revealed that the other preferential sites were small intestine, mediastinum, epidural site, uterus, and ovary, i.e., sites often difficult for the detection and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytic sarcoma develops in 2-8 % of patients with acute nonlymphoblastic leukemia (ANLL). 1,2 It usually occurs concomitantly with or after the onset of ANLL. 3,4 On rare occasions, it evolves before the onset of ANLL, and among these cases it often is misdiagnosed as malignant lymphoma.…”
mentioning
confidence: 99%
“…1,2 In many cases, granulocytic sarcoma emerges at the time of relapse of myeloid neoplasm. In the present case, however, the tumor occurred concurrent with the onset of myeloid leukemia, and such pattern of onset is relatively uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytic sarcoma is a very rare disease, comprising approximately 2% to 9% of all patients with acute myeloid leukemia (AML). 1,2 The histologic morphology of granulocytic sarcoma may lead to its misdiagnosis as malignant lymphoma, 3,4 and early diagnosis of this tumor is very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…GS develops in 2-8% of patients with AML [1,2] and it could manifest in any anatomical location including the skin [3], lymph nodes [4,5], gastro-intestinal tract [6,7], bone [8], soft tissue [9], ovaries, and brain [10]. The majority of GS do not cause clinically significant signs and symptoms.…”
mentioning
confidence: 99%